1985
DOI: 10.1111/j.1365-3024.1985.tb00098.x
|View full text |Cite
|
Sign up to set email alerts
|

A limiting dilution assay for quantifying Leishmania major in tissues of infected mice

Abstract: A limiting dilution assay for the quantification of Leishmania major in infected mouse tissue was developed. The assay was found to be both sensitive and reliable, and, due to its design, could be scored either visually or following the incorporation of 3H-thymidine by the growing parasites. Results are presented in which the assay was employed to enumerate L. major in the tissues of susceptible (BALB/c) and resistant (CBA) mice at intervals after infection with L. major. It was found that parasites could be d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
364
0
9

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 490 publications
(378 citation statements)
references
References 13 publications
5
364
0
9
Order By: Relevance
“…1). Furthermore, the numbers of viable parasites recovered after culture in vitro of footpad tissue under limiting dilution condition (32) confirmed that although parasite growth was controlled in V␤4 CD4 ϩ T cell-deficient BALB/c mice comparably to that in resistant C57BL/6 mice (ϳ200 parasites/footpad) 6 wk after infection, footpad lesions of V␤4 CD4 ϩ T cell-deficient BALB/c mice treated with IL-4 during the first 64 h of infection contained numbers of parasites (ϳ10 8 ) similar to those found in control BALB/c mice.…”
Section: Discussionmentioning
confidence: 99%
“…1). Furthermore, the numbers of viable parasites recovered after culture in vitro of footpad tissue under limiting dilution condition (32) confirmed that although parasite growth was controlled in V␤4 CD4 ϩ T cell-deficient BALB/c mice comparably to that in resistant C57BL/6 mice (ϳ200 parasites/footpad) 6 wk after infection, footpad lesions of V␤4 CD4 ϩ T cell-deficient BALB/c mice treated with IL-4 during the first 64 h of infection contained numbers of parasites (ϳ10 8 ) similar to those found in control BALB/c mice.…”
Section: Discussionmentioning
confidence: 99%
“…Lesion size was monitored on a weekly basis for 10 wk using a digital caliper (Thomas Scientific). Parasite load was determined using a quantitative limiting dilution assay as described previously (18).…”
Section: Neutrophil Depletion Intradermal Inoculation and Lesion Mementioning
confidence: 99%
“…A fragment from each organ was collected to be used for parasite quantification. Quantitative limiting dilution culture was performed as described by Titus et al (1985) and modified by Marques-da-Silva et al (2005). One weighed fragment from each organ (liver and spleen) was homogenized in a tissue grinder and suspended in 500 μL of Grace's Insect Medium (Gibco BRL, Grand Island, NY, USA) supplemented with 10% heat-inactivated foetal calf serum (FCS) (Cripton, Andradina, SP, Brazil), 2 mM L-glutamine (Gibco BRL) and 100 U/mL penicillin G potassium (USB Corporation, Cleveland, OH, USA), pH 6.5 in 96-well flatbottom microtitre plates (160 μL per well).…”
Section: Animals Diets and Experimental Infection -Femalementioning
confidence: 99%